NPY signalling in early osteoblasts controls glucose homeostasis - Nicola J. Lee; Amy D. Nguyen; Ronaldo F. Enriquez; Jude Luzuriaga; Mohammed Bensellam; Ross Laybutt; Paul A. Baldock; Herbert Herzog (Elsevier, 2015)
Objective: The skeleton has recently emerged as an additional player in the control of whole-body glucose metabolism; however, the mechanism behind this is not clear. Methods: Here we employ mice lacking neuropeptide Y, Y1 receptors solely in cells of the early osteoblastic lineage (Y1f3.6Cre), to examine the role of osteoblastic Y1 signalling in glycaemic control. Results: Y1f3.6Cre mice not only have a high bone mass phenotype, but importantly also display altered glucose homeostasis; significantly decreased pancreas weight, islet number and pancreatic insulin content leading to elevated glucose levels and reduced glucose tolerance, but with no effect on insulin induced glucose clearance. The reduced glucose tolerance and elevated bone mass was corrected in Y1f3.6Cre mice by bone marrow transplant from wildtype animals, reinforcing the osteoblastic nature of this pathway. Importantly, when fed a high fat diet, Y1f3.6Cre mice, while equally gaining body weight and fat mass compared to controls, showed significantly improved glucose and insulin tolerance. Conditioned media from Y1f3.6Cre osteoblastic cultures was unable to stimulate insulin expression in MIN6 cells compared to conditioned media from wildtype osteoblast, indicating a direct signalling pathway. Importantly, osteocalcin a secreted osteoblastic factor previously identified as a modulator of insulin secretion was not altered in the Y1f3.6Cre model. Conclusion: This study identifies the existence of other osteoblast-derived regulators of pancreas function and insulin secretion and illustrates a mechanism by which NPY signalling in bone tissue is capable of regulating pancreatic function and glucose homeostasis.